The Mkx- TGF-β pathway induced the development of the myodural bridge complex in SD rats - Li, Ji-Hang; Jiang, Wen-Bin; Zhang, Lu; Liu, Yun-Feng; Sun, Yi-Tong; Lai, Hua-Xun; Alam Shah, M. Adeel; Ma, Wei; Li, Chan; Gilmore, Campbell; Zhang, Jian-Fei; Sui, Hong-Jin (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveThe myodural bridge complex (MDBC) is a tendon-like structure highly conserved during vertebrate evolution, suggesting it plays an important physiological role. Substantial evidence indicates that the MDBC may contribute to cerebrospinal fluid (CSF) circulation by generating mechanical force. Studying its developmental process may offer new insights into CSF dynamics and lead to improved strategies for diagnosing and treating neurodegenerative diseases.Materials and MethodsThis study utilized utilized lentiviral plasmids to either knockdown or overexpress the Mkx gene in newborn Sprague-Dawley rats (SD) rats, establishing three groups: control, overexpression group, and interference group. Suboccipital injections were performed at birth. Histological staining and qPCR were conducted at multiple time points to assess the morphological and genetic impacts of Mkx modulation on the development of the MDBC.ResultsTransfection efficiency was confirmed by Green fluorescent protein (GFP) expression quantification, in vivo bioluminescent imaging, and Western blot validation in all experimental cohorts. Mkx knockdown exhibited diminished collagen fiber development accompanied by compensatory hyperplasia of occipital periosteum-derived fibrous tissues. Transcriptomic analysis revealed that Mkx overexpression upregulated tendon-related genes (Scx, Egr1) and downregulated myogenic regulators (Myod), with inverse expression patterns observed in knockdown models. Pathway gene analysis identified the TGF-β signaling cascade and associated mechanosensitive genes as central regulators of the MDBC.ConclusionMkx exerts bidirectional regulation on MDBC development by modulating the TGF-β signaling pathway. Overexpression of Mkx promotes collagen deposition and structural reinforcement in MDBC through coordinated molecular mechanisms: upregulating Scx/Egr1 expression, downregulating Myod, and inducing hyperplastic growth of deep fascial fibers in the rectus capitis dorsal minor muscle (RCDmi). Conversely, Mkx suppression maintains tissue integrity through three synergistic mechanisms: upregulating Myod expression, inducing MDBC fiber proliferation, and facilitating adaptive remodeling of the posterior atlanto-occipital membrane (PAOM). At the molecular level, Mkx coordinates differentiation processes through dynamic equilibrium of Scx/Egr1/Myod expression profiles while constructing regulatory networks that couple biomechanical-chemical signals via TGF-β pathway activation.